PENERAPAN MODEL KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN IPAS DI KELAS IV SDI NAMOSAIN - Suy, Nanda Talita Chelzia; Taneo, Silvester P.; Koro, Maxsel (Universitas Nusa Cendana, 2024)
This research aims to improve learning outcomes in class IV SDI Namosain by implementing the jigsaw-type cooperative learning model. The method in this research is classroom action research through four stages, namely; planning, implementation, observation and testing, and reflection. The subjects of this research were 22 class IV students. This research is located at SDI Namosain, Kupang City. The research results showed that in cycle I as many as 13 students completed with a completion percentage of 59.09%. Meanwhile, 9 students did not complete with a completion percentage of 40.91%. Student observation results were 63.14 and teacher observation results were 72.7. In cycle II, 20 students completed with a completion percentage of 90.91% and there were only 2 students who did not complete with a percentage of 9.09%. Student observation results were 78.90, and teacher observation results were 95.4. In this way, these 2 people will be given enrichment or additional learning by the teacher. Based on the research results, it can be concluded that using the jigsaw-type cooperative model can improve learning outcomes for class IV students at SDI Namosain, Kupang City